Sampling density and proportion for the characterization of the variability of Oxisol attributes on different materials - Siqueira, D. S. [UNESP]; Marques, J. [UNESP]; Pereira, G. T. [UNESP]; Barbosa, R. S. [UNESP]; Teixeira, D. B. [UNESP]; Peluco, R. G. [UNESP] (Elsevier B.V., 2014)
Establishing a soil sampling plan is one of the most important stages for providing the detailed information required for sustainable land management. This study aims to investigate the most appropriate sampling density and proportion for the characterization of Oxisol attributes on different materials, using the magnetic susceptibility (MS). The studied area is located in Sao Paulo State, Brazil, in Guatapard Town and its size is 380 ha. To evaluate the subsampling effect in the variability description, 60 samples were collected from part of the area (150 ha) in the density of one point per 2.5 ha, using both simple sampling and subsamples with three points. Different sampling densities were obtained (3; 4; 5; 6; 7; 8; and one point per 9 ha) by the exclusion of points. The evaluated attributes were: clay content; base saturation and MS at 0.00-0.25 and 0.25-0.50 m depths. There were no differences among spatial variability maps generated from either simple or subsamples. This information might precede a change in the sampling system for the agricultural industry. The minimal sampling density required so that there is no loss in the spatial variability representativeness was one point per 7 ha. MS may be used to upgrade clay content estimates in the sampling proportion of three points of MS for per clay point (one point per 2.5 ha for MS: one point per 7 ha). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Sampling plan; Magnetic susceptibility; Stratified sampling; Agreement index